Peningkatan Kapasitas Manajemen Risiko Keuangan UMKM Berbasis Wisata melalui Penyuluhan dan Pendampingan di Pantai Carita - Aep Saefullah; Ahmad Fadli; Ramadani Pardian; Devid Putra Arda; Nizar Zulkarnain; Farhat Abas; Fahri Fahri; Fuad Gagarin Siregar; Tuti Herawati; Neila Aisha; Moh. Tahang; Cinta Rahmi; Tetty Nur Intan Rifia; Abdul Muhaimin (Journal of Community Research & Engagement, 2026)
Tourism-based micro, small, and medium enterprises (MSMEs) play a crucial role in supporting local economic activities, particularly in coastal tourism areas such as Pantai Carita. However, their high dependence on tourist arrivals exposes them to significant financial risks, including income instability, rising operational costs, and cash flow constraints. This community service activity aims to strengthen the financial risk management capacity of MSME actors through practical and context-based interventions. The program was conducted on 15–17 December 2025, involving 50 tourism MSME actors from culinary, rental, and service sectors. A participatory approach was applied through counseling and direct mentoring. Counseling sessions covered financial risk concepts and simple bookkeeping, while mentoring focused on the practical implementation of daily cash flow recording and risk identification. The results show significant quantitative improvements: understanding of financial risk increased from 22% to 78%, daily cash flow recording from 18% to 72%, and emergency fund allocation from 10% to 60%. In addition, the ability to identify business risks rose from 25% to 80%, while financial-based decision making improved from 28% to 73%. These results indicate that simple and practical interventions effectively enhance financial awareness, managerial capability, and adaptive behavior of MSMEs in managing business risks